Taxonomy and distribution of sea anemones (Cnidaria: Actiniaria, Corallimorpharia) from deep water of the northeastern Pacific - Eash-Loucks, W. E.; Fautin, D. G. (Zootaxa, 2012)
Sea anemones sensu lato (members of cnidarian orders Actiniaria and Corallimorpharia) occurring in water of the northeastern Pacific Ocean greater than 1,000 m (to the abyssal plain) are poorly known. Based on the literature and specimens we examined in the four largest collections of animals from this area, we estimate that approximately 35 species occur in these deep-water habitats and fewer than half have been documented there. Of the largest and most abundant epibenthic species, based on morphology, we identified two species of Corallimorpharia (both previously known) and 12 of Actiniaria (three new). Half the sea anemone species are widely distributed: Actinauge verrillii McMurrich, 1893, Actinoscyphia groendyki n. sp., Actinostola faeculenta (McMurrich, 1893), Bathyphellia australis Dunn, 1983, Liponema brevicorne (McMurrich, 1893), Metridium farcimen (Brandt, 1835), and Monactis vestita (Gravier, 1918). The others are known only from the northeastern Pacific Ocean: Corallimorphus pilatus Fautin, White, and Pearson, 2002, Corallimorphus denhartogi Fautin, White, and Pearson, 2002, Anthosactis nomados White, Wakefield Pagels, and Fautin, 1999, Bolocera kensmithi n. sp., Paraphelliactis pabista Dunn, 1982, Sagartiogeton californicus (Carlgren, 1940) (for which we designate a neotype), and Sicyonis careyi n. sp. A naturally occurring oxygen minimum zone (OMZ) off Oregon is expanding, and the marine life living within its virtually anoxic areas is threatened. Nine of the species we examined occur within the current depth range of the OMZ and may be threatened if the OMZ continues to strengthen and expand.